Meningkatkan Kesadaran dan Akses Kesehatan Mental pada Mahasiswa melalui Skrining pada Telemedicine Halodoc - Kharomah, Larasati Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the role of app-based depression screening, such as Halodoc as a solution for early detection and intervention in college students. Depression in college students often escapes identification. This can negatively impact their academic performance and quality of life. Through a descriptive literature study, this paper demonstrates that students need mental health services that are easily accessible, maintain privacy, and involve professionals. Mental health apps meet this need by providing brainstorming consultation features, depression testing (using the PHQ-9), and educational articles. Early screening allows for rapid and appropriate intervention, preventing the condition from worsening and continuing into adulthood. Despite challenges such as stigma and privacy issues, these services offer great opportunities to responsibly improve students’ mental well-being.